SELEKSI CALON INDUK BERDASARKAN NILAI PEMULIAAN BOBOT SAPIH KAMBING KACANG DI KECAMATAN NATAR, KABUPATEN LAMPUNG SELATAN - Fahrudi Hamid; Idalina Harris; Didik Rudiono (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
Breeding Value is an evaluation of the quality of animal genetics for a certain character which isgiven relatively based on its position in population. This study aimed to determine the value ofheritability and repeatability of weaning weight of Kacang goats, to determine the weaning weightand the breeding value of each individual mather do, and to determine the individual mather dowhich had the highest breeding value of weaning weight. This study used survey method to obtainthe subject matters, which comprised 30 female parentstock which had recording of litter age,pedigree of males, and kids of female samples which had recording of birth weight, type of birth,type of maintenance, and weaning weight of the first and the second birth.The result of this study showed that the average of corrected weaning weight was 9,574±0,97 kg;the heritability value of weaning weight was 0,011±0,000; the repeatability of weaning weight was0,061; the average of breeding value of weaning weight was 9,613±0,02. Based on the result ofthis study, it was known that 19 (51%) of 30 female parentstock of Kacang goats had breedingvalue over the average, and 5 female parentstock with the highest breeding value of weaningweight were prioritized, they were female parentstock with codes D1 with breeding value was9,673; N1 was 9,633; H1 was 9,629; I1 was 9,629; S1 was 9,628 in the study location.